2022
DOI: 10.1007/s12237-022-01116-3
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Trophic Niche and Resource Use Dynamics Across Multiple American Horseshoe Crab (Limulus polyphemus) Populations and Age Groups

Abstract: Horseshoe crabs (Limulus polyphemus) exhibit ontogenetic and geographic variability in migratory patterns, yet the implications of movement on their resource use dynamics remain poorly understood. Here, we evaluate horseshoe crab resource use across ontogeny (instars 14–18 and adults), sex, seasons, and between two spatially distinct populations that exhibit different migratory patterns. Multi-tissue stable isotope analyses of carbon, nitrogen, and sulfur were used to examine (1) ontogenetic and sex-specific v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 98 publications
(127 reference statements)
0
5
1
Order By: Relevance
“…However, our results differed from those of Lemons et al (2012) with respect to δ 15 N. Lemons et al (2012) found that whole blood samples treated with sodium heparin were significantly enriched in 15 N relative to untreated samples whereas our study found no significant difference between δ 15 N values in treated and untreated samples. Lemons et al (2012) did not assess δ 34 S, but our findings with respect to δ 34 S values differed from those of Bopp et al (2022), who found no significant difference in δ 34 S between treated and untreated samples of Atlantic Horseshoe Crab blood. These differences in findings across the literature highlight that isotopic factors can vary depending on the taxa (2007), the addition of the anticoagulant EDTA to avian whole blood samples altered δ 13 C and δ 15 N values by 0.57‰ and 0.63‰, respectively, though this effect was considered negligible relative to field signatures.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…However, our results differed from those of Lemons et al (2012) with respect to δ 15 N. Lemons et al (2012) found that whole blood samples treated with sodium heparin were significantly enriched in 15 N relative to untreated samples whereas our study found no significant difference between δ 15 N values in treated and untreated samples. Lemons et al (2012) did not assess δ 34 S, but our findings with respect to δ 34 S values differed from those of Bopp et al (2022), who found no significant difference in δ 34 S between treated and untreated samples of Atlantic Horseshoe Crab blood. These differences in findings across the literature highlight that isotopic factors can vary depending on the taxa (2007), the addition of the anticoagulant EDTA to avian whole blood samples altered δ 13 C and δ 15 N values by 0.57‰ and 0.63‰, respectively, though this effect was considered negligible relative to field signatures.…”
Section: Discussioncontrasting
confidence: 92%
“…For each isotope, denoted as the jth group, and individual, denoted as the ith group, we computed the difference (D) between the treatment and control sample as: D ji = X treatment − X control , where X represents δ 13 C, δ 15 N or δ 34 S and where D ji ~N(μ j , σ 2 ), denoting that D is drawn from a normal distribution with mean μ j and variance σ 2 . We used a semi-informative prior for μ (μ j ~N(0,1)) with prior information coming from Lemons et al (2012) and Bopp et al (2022), who found that differences between treatment and control groups were between 0 and 1‰ for whole blood. We chose a semi-informative prior, rather than an uninformative prior, as the incorporation of prior information into Bayesian models increases the precision of parameter estimations (Banner et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations